Evaluation of ovarian response prediction according to age and serum AMH levels in IVF cycles: a retrospective analysis - Pillai, Sathy M.; Mahabalshetti, Nishtha A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Increasing female literacy and employment have resulted in a clear rise in the age at which women conceive. As fertility starts to decline with advancing age more and more number of women are facing the problem of infertility and are seeking medical attention to overcome this problem. A number of ovarian reserve tests were developed to overcome this problem. Recent studies indicate that anti mullerian hormone is a promising marker for predicting ovarian reserve and pregnancy outcome. Methods: A retrospective study conducted at SAMAD IVF hospital, Trivandrum, Kerala. The aim of this study was to assess the influence of age on Anti-Mullerian Hormone (AMH) in ART (assisted reproductive technology) program outcomes and determine whether AMH levels and age predict the availability of total oocytes and MII oocytes retrieved and good quality of embryos. Ninety-six subjects in the age group of 25 to 40 years were included and underwent controlled ovarian stimulation (COS) and later intracytoplasmic sperm injection (ICSI) was performed. Results: In present study, it is seen that age and AMH (anti-mullerian hormone) have negative correlation. In accordance to AMH, total number of oocytes retrieved, MII oocytes, total number of embryos and grade A embryos were higher in AMH group (>5ng/ml). Total embryos for cryopreservation were lower in age group of 31-35yrs and 36-40yrs with least AMH value as compared to younger age group, good quality of embryos was higher in age group of 25-30yrs with 1.5-5 and >5 AMH group. Conclusions: Serum AMH is an important ovarian reserve test to predict response in ART cycles. Age is an independent marker in terms of quality of oocytes retrieved. We conclude that age and AMH have negative correlation. Hence, AMH can predict number of oocytes retrieved but age predicts quality of oocytes and embryos.